Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Ask your questions and receive precise answers from experienced professionals across different disciplines. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To transform the given cubic equation [tex]\(2x^3 - 9x^2 - 6 = 0\)[/tex] into a form where the second term is eliminated, we need to apply a specific substitution to [tex]\(x\)[/tex].
### Step-by-Step Procedure
1. Identify the General Form:
Consider the cubic polynomial in the form [tex]\(ax^3 + bx^2 + cx + d = 0\)[/tex]. In our problem, [tex]\(a = 2\)[/tex], [tex]\(b = -9\)[/tex], [tex]\(c = 0\)[/tex], and [tex]\(d = -6\)[/tex].
2. Substitution Method:
To eliminate the second term, [tex]\(bx^2\)[/tex], we use the substitution [tex]\(x = y + h\)[/tex] where [tex]\(h\)[/tex] is a constant that needs to be determined.
3. Perform the Substitution:
Substitute [tex]\(x = y + h\)[/tex] into the equation:
[tex]\[ 2(y+h)^3 - 9(y+h)^2 - 6 = 0 \][/tex]
4. Expand the Terms:
Let's expand [tex]\((y+h)^3\)[/tex] and [tex]\((y+h)^2\)[/tex]:
[tex]\[ (y+h)^3 = y^3 + 3hy^2 + 3h^2y + h^3 \][/tex]
[tex]\[ (y+h)^2 = y^2 + 2hy + h^2 \][/tex]
Therefore,
[tex]\[ 2(y+h)^3 = 2(y^3 + 3hy^2 + 3h^2y + h^3) = 2y^3 + 6hy^2 + 6h^2y + 2h^3 \][/tex]
[tex]\[ -9(y+h)^2 = -9(y^2 + 2hy + h^2) = -9y^2 - 18hy - 9h^2 \][/tex]
5. Combine the Terms:
Substitute these back into the original equation:
[tex]\[ 2(y^3 + 6hy^2 + 6h^2y + 2h^3) - 9(y^2 + 2hy + h^2) - 6 = 0 \][/tex]
Simplify the expression:
[tex]\[ 2y^3 + 6hy^2 + 6h^2y + 2h^3 - 9y^2 - 18hy - 9h^2 - 6 = 0 \][/tex]
Group the terms:
[tex]\[ 2y^3 + (6h - 9)y^2 + (6h^2 - 18h)y + (2h^3 - 9h^2 - 6) = 0 \][/tex]
6. Eliminate the Second Term:
For the second term to be zero, the coefficient of [tex]\(y^2\)[/tex] must be zero:
[tex]\[ 6h - 9 = 0 \][/tex]
Solve for [tex]\(h\)[/tex]:
[tex]\[ 6h = 9 \\ h = \frac{9}{6} = \frac{3}{2} \][/tex]
### Conclusion
The roots are to be diminished by [tex]\(\frac{3}{2}\)[/tex].
Thus, the correct choice is:
(c) [tex]\(\frac{3}{2}\)[/tex]
### Step-by-Step Procedure
1. Identify the General Form:
Consider the cubic polynomial in the form [tex]\(ax^3 + bx^2 + cx + d = 0\)[/tex]. In our problem, [tex]\(a = 2\)[/tex], [tex]\(b = -9\)[/tex], [tex]\(c = 0\)[/tex], and [tex]\(d = -6\)[/tex].
2. Substitution Method:
To eliminate the second term, [tex]\(bx^2\)[/tex], we use the substitution [tex]\(x = y + h\)[/tex] where [tex]\(h\)[/tex] is a constant that needs to be determined.
3. Perform the Substitution:
Substitute [tex]\(x = y + h\)[/tex] into the equation:
[tex]\[ 2(y+h)^3 - 9(y+h)^2 - 6 = 0 \][/tex]
4. Expand the Terms:
Let's expand [tex]\((y+h)^3\)[/tex] and [tex]\((y+h)^2\)[/tex]:
[tex]\[ (y+h)^3 = y^3 + 3hy^2 + 3h^2y + h^3 \][/tex]
[tex]\[ (y+h)^2 = y^2 + 2hy + h^2 \][/tex]
Therefore,
[tex]\[ 2(y+h)^3 = 2(y^3 + 3hy^2 + 3h^2y + h^3) = 2y^3 + 6hy^2 + 6h^2y + 2h^3 \][/tex]
[tex]\[ -9(y+h)^2 = -9(y^2 + 2hy + h^2) = -9y^2 - 18hy - 9h^2 \][/tex]
5. Combine the Terms:
Substitute these back into the original equation:
[tex]\[ 2(y^3 + 6hy^2 + 6h^2y + 2h^3) - 9(y^2 + 2hy + h^2) - 6 = 0 \][/tex]
Simplify the expression:
[tex]\[ 2y^3 + 6hy^2 + 6h^2y + 2h^3 - 9y^2 - 18hy - 9h^2 - 6 = 0 \][/tex]
Group the terms:
[tex]\[ 2y^3 + (6h - 9)y^2 + (6h^2 - 18h)y + (2h^3 - 9h^2 - 6) = 0 \][/tex]
6. Eliminate the Second Term:
For the second term to be zero, the coefficient of [tex]\(y^2\)[/tex] must be zero:
[tex]\[ 6h - 9 = 0 \][/tex]
Solve for [tex]\(h\)[/tex]:
[tex]\[ 6h = 9 \\ h = \frac{9}{6} = \frac{3}{2} \][/tex]
### Conclusion
The roots are to be diminished by [tex]\(\frac{3}{2}\)[/tex].
Thus, the correct choice is:
(c) [tex]\(\frac{3}{2}\)[/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.